Killing (Life)Time: A study on the Experience of Time in Prision - Pablo Leandro Ciocchini (Sortuz)
Prison emerged in its early forms in Europe in the mid 16th century and it spread together with capitalism. It operates by imposing to the individual a particular rigid time regime in an extremely limited spatial environment. Although society has been speeding itself up during the last forty years due to the introduction of new information and transportation technologies, prison conserved its own archaic time resulting in a ‘gap’ between society’s and prison’s time regime. The study presented in this article seeks to explore how this temporal ‘gap’ is experienced by prisoners in post-modern societies such as the Spanish and the British ones. The experience of time is not measurable so instead of the traditional quantitative approach used in ‘time use surveys’ this study scrutinises the inmates’ time experience from a qualitative approach. The aim is to describe the kind of time that social practices inside this institution produce through the voices of those who have been incarcerated and through their experiences after recovering their freedom. The narratives used include qualitative ‘face to face’ interviews to prisoners of Spain as well as autobiographical narratives from prisoners of Great Britain.